The Flash. Vol. 12, Death and the speed force - Williamson, Joshua (DC Comics, 2020)
"It's "The Flash: Year One" as Barry Allen races back to the start of his crime-fighting career to relearn the lessons of what it means to be the Fastest Man Alive. Forensic scientist Barry Allen feels helpless in his life in Central City--he's always catching criminals after they've committed their crimes. All that changes one fateful night when Barry is struck by a bolt of lightning and doused in chemicals. When he wakes from a coma, he realizes he can run at incredible speeds. Can Barry master these powers and be the hero his city needs...or will the powers burn through him? His struggles lead him into the far future, where a version of the Flash he will someday become shows him the true path of the hero--and helps him prepare for the emergence of the gang of villains known as the Rogues."--